2017
DOI: 10.5539/ijbm.v12n8p227
|View full text |Cite
|
Sign up to set email alerts
|

The Development Strategy of Packaged Pempek Industry

Abstract: The purpose of this study is to examine the factors that play a role in the development of pempek quality favored by consumers and to study internal and external factors that influence the development of pempek processing industry and its implications for strengths, weaknesses, opportunities and threats as well as formulate alternative development strategies for Pempek industry.The sampling technique used in this study is simple random sampling with a sample area of 95 respondents consisting of 10 pempek proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Some Pempek establishments are very popular nationally and have opened franchised branches in many cities (65). In South Sumatra, Pempek is sold mainly as foodstuff gifts or souvenirs for visitors from other Indonesian cities (66). In this case, Pempek is commonly sold as frozen ready-tocook dumplings in vacuum packagings along with concentrated kuah cuko that needs further diluting upon consumption (Figure 8F).…”
Section: Current Development Of Pempekmentioning
confidence: 99%
“…Some Pempek establishments are very popular nationally and have opened franchised branches in many cities (65). In South Sumatra, Pempek is sold mainly as foodstuff gifts or souvenirs for visitors from other Indonesian cities (66). In this case, Pempek is commonly sold as frozen ready-tocook dumplings in vacuum packagings along with concentrated kuah cuko that needs further diluting upon consumption (Figure 8F).…”
Section: Current Development Of Pempekmentioning
confidence: 99%
“…Boiled pempek has relatively high moisture content 60-67% [3]. Shelf life of boiled pempek in room temperature is only one day [4,5]. The short shelf life of pempek caused by high nutrition contents which had degradation by microbes into volatile components such as trimethylamine, H2S, CO2, ammonium that caused stink and rancidity smells [5].…”
Section: Introductionmentioning
confidence: 99%
“…Shelf life of boiled pempek in room temperature is only one day [4,5]. The short shelf life of pempek caused by high nutrition contents which had degradation by microbes into volatile components such as trimethylamine, H2S, CO2, ammonium that caused stink and rancidity smells [5]. To extend shelf life of pempek, several studies have reported some research on dried pempek.…”
Section: Introductionmentioning
confidence: 99%